TOLERANȚA EUROPEANĂ – „WELCOME CULTURE” – UN ATU SAU „CĂLCÂIUL LUI AHILE”? (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
European tolerance – „welcome culture” – an asset or „Achilles heel”?The purpose of this article is to sound the alarm about Europe’s open door  policy. The old continent deserves all the credit for its hospitable spirit  towards migrants, but if the gates continue to be wide open, without prior  pre-selection, we will wake up too late with the Trojan Horse within our walls.  This article is against Islamophobia as much as it is against anti-Semitism or  against the European extreme (radical) right. A balanced approach to the  migration phenomenon is not the same as taking no stance. This  phenomenon is like a double-edged sword. On the one hand, it gives you the  impression that it can solve the aging of the European population and the  labor force crisis, on the other hand, it risks destabilizing Europe’s identity.